Unsteady MHD flow and heat transfer over a stretching/shrinking permeable sheet with ohmic heating - Md Ali, Zaileha; Jamaruddin, Nurulnabila; Soid, Siti Khuzaimah; Mohd Idris, Nur Aziean; Udin, Md Nizam; Ismail, Nur Zahidah (EDUCATUM Journal of Science, Mathematics and Technology, 2019)
The problem of an unsteady magnetohydrodynamics (MHD) and heat transfer over a stretching/shrinking permeable sheet with ohmic heating is studied in this paper.  Using a nonlinear partial differential equations system, the physical problem is modeled and transformed into ordinary differential equations using similarity transformation.  Along with the boundary conditions, the equations are solved numerically using bvp4c in the MATLAB software and a comparison with previous literature shows an excellent agreement.  The effect of suction parameter, unsteady parameter and magnetic parameter in porous plate are discussed.  The results show that the velocity profile and skin friction coefficient increases when suction parameter increases.  Furthermore, the increase in magnetic and unsteady parameters resulted in the increase in the velocity profile and the skin friction coefficient respectively.